Fuentes textuales de la Rhetorica Ecclesiastica de Agostino Valier - López Muñoz, Manuel (2020)
This paper proposes a source analysis of Agostino Valier’s Rhetorica Ecclesiastica. The methodology is adapted from the approaches developed by Morawski, Díaz Lavado and Herrero Salgado, and may be applied to the study of other technical treatises. First of all, intertexts are classified according to their typology and finality: typologically, intertexts are divided into textual quotations, quotations ad sensum, references, and allusions; in terms of finality, intertexts are divided into argumentation sources, support of argumentation sources, discourse elements, and definitions. After a description of the relationship between the textual sources and the way Valier uses them, a more accurate vision on his thought arises, thus avoiding a priori statements on the relevance of the authors and works cited in the Rhetorica Ecclesiastica.
Keywords: Valier, Agostino, -- 1531-1606; Retórica